1986
DOI: 10.1177/016235328600900203
|View full text |Cite
|
Sign up to set email alerts
|

Attribution for Academic Successes and Failures of Students Participating and Not Participating in Programs for the Gifted

Abstract: The purpose of this study was to examine differences in attribution for the academic successes and failures of high school students participating in and not participating in programs for the gifted. Students were administered the Intellectual Achievement Responsibility Scale. The findings indicate that students participating in programs for the gifted tend to attribute their successes to their own effort and ability to a greater degree than students not participating in programs for the gifted. Implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Their results suggest that the internal barriers might be interrelated and that the group identified with low social self-esteem was the group least conducive to fulfillment of career potential. Kammer (1986) found gifted students in special programs report greater personal responsibility for outcome than non-participants but found no gender difference for attributions in gifted students. On the other hand, Subotnik (1988), in a study of 146 high school winners of the 1983 Westinghouse Science Talent Search, found a much higher proportion of females than males chose dedication to work rather than intelligence or creativity as the most admirable quality.…”
Section: Achievement-related Motivations Of Gifted Females/malesmentioning
confidence: 76%
“…Their results suggest that the internal barriers might be interrelated and that the group identified with low social self-esteem was the group least conducive to fulfillment of career potential. Kammer (1986) found gifted students in special programs report greater personal responsibility for outcome than non-participants but found no gender difference for attributions in gifted students. On the other hand, Subotnik (1988), in a study of 146 high school winners of the 1983 Westinghouse Science Talent Search, found a much higher proportion of females than males chose dedication to work rather than intelligence or creativity as the most admirable quality.…”
Section: Achievement-related Motivations Of Gifted Females/malesmentioning
confidence: 76%
“…When identified as gifted, children may learn that intelligence is a capacity you either have or do not have, thus contributing to the development of a fixed mind-set. In addition, for those identified as gifted, it might be self-serving to attribute their superior achievement to the fixed quality they happen to possess; indeed, identified gifted students were found to be more inclined to attribute their successes to internal causes (e.g., ability) than nonidentified students with similar ability (Kammer, 1986).…”
Section: Introductionmentioning
confidence: 99%